A randomised controlled trial of preinduction cervical ripening-dinoprostone versus foleys catheter - M., Mumtaj; M., Harilakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical ripening before induction of labour in women with unfavourable cervix is essential to shorten the induction to delivery interval and avoid unnecessary interventions. Methods: The study was carried out at Raja Sir Ramasamy Mudaliar hospital, Chennai during the period August 2012 to July 2013. 200 antenatal women were recruited and randomly allocated to Foleys and prostaglandin E2 gel group for induction. The change in bishops score, induction to delivery interval, mode of delivery, vaginal delivery within 24 hours, maternal complications, fetal outcome between both groups were compared. Results: The commonest indication for induction in both groups was postdated pregnancy followed by oligohydramnios in Foleys group and preeclampsia in PGE2 group. Foleys catheter induction improves bishops score better compared to PGE2 gel whereas PGE2 gel causes a significant reduction in the mean induction to delivery interval between the two groups. However, there was no significant difference between mean caesarean deliveries between the two groups. In both Foleys and the PGE2 group, failed induction was the commonest indication for caesarean section. The number of patients delivering vaginally within 24 hrs was similar between the two groups. Conclusions: Though prostaglandins are a better method of induction, this study shows that Foleys induction has reduced side effects and is also cost effective, making it a superior method for cervical ripening.